Lattice Boltzmann simulations of drying suspensions of soft particles - Wouters, M.; Aouane, O.; Sega, M.; Harting, Jens (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2021)
The ordering of particles in the drying process of a colloidal suspension is crucial in determining the properties of the resulting film. For example, microscopic inhomogeneities can lead to the formation of cracks and defects that can deteriorate the quality of the film considerably. This type of problem is inherently multiscale and here we study it numerically, using our recently developed method for the simulation of soft polymeric capsules in multicomponent fluids. We focus on the effect of the particle softness on the film microstructure during the drying phase and how it relates to the formation of defects. We quantify the order of the particles by measuring both the Voronoi entropy and the isotropic order parameter. Surprisingly, both observables exhibit a non-monotonic behaviour when the softness of the particles is increased. We further investigate the correlation between the interparticle interaction and the change in the microstructure during the evaporation phase. We observe that the rigid particles form chain-like structures that tend to scatter into small clusters when the particle softness is increased. This article is part of the theme issue 'Progress in mesoscale methods for fluid dynamics simulation'.
CRIS-Team WoS Importer:2021-09-17
Keywords: clusters; lattice Boltzmann simulation; capillary interactions; soft particles suspensions; thin films